Biopolitics in Central and Eastern Europe in the 20th century
1 online resource (vi, 267 pages)
Keywords: "The field of biopolitics encompasses issues from health and hygiene, birth rates, fertility and sexuality, life expectancy and demography, to eugenics and racial regimes. This book is the first to provide a comprehensive view on these issues for Central and Eastern Europe in the 20th century. The cataclysms of imperial collapse, World War(s) and the Holocaust but also the rise of state socialism after 1945 provided extraordinary and distinct conditions for the governing of life and death. The volume collects the latest research and empirical studies from the region to showcase the diversity of biopolitical regimes in their regional and global context - from hunger relief for Hungarian children after World War I to abortion legislation in communist Poland. It underlines the similarities as well, demonstrating how biopolitical strategies in this area often revolved around the notion of an endangered nation; and how ideological schemes and post-imperial experiences in Eastern Europe further complicate a "western" understanding of democratic participatory and authoritarian repressive biopolitics. The new geographical focus invites scholars and students of social and human sciences to reconsider established perspectives on the history of population management and the history of Europe"--